61.6k views
3 votes
What is the inverse of the function f(x) = 2x + 1? 1 1 Oh(x) = 2 2 1 oh(x) = O n(x) = 5x + 199 3x-2 - 3x + 2 h(x) = x + 2​

User Skypjack
by
6.5k points

1 Answer

3 votes

Answer:


f^(-1)(x) =
(x-1)/(2)

Explanation:

let y = f(x) and rearrange making x the subject, that is

y = 2x + 1 ( subtract 1 from both sides )

y - 1 = 2x ( divide both sides by 2 )


(y-1)/(2) = x

Change y back into terms of x with x =
f^(-1)(x) , thus


f^(-1)(x) =
(x-1)/(2)

User Bobetko
by
6.7k points